Breaking barriers and building bridges: Police responses to same-sex partner abuse in England and Wales - BUTTERWORTH, KATE (2018)
Partner abuse is now recognised as a problem that affects people within same-sex relationships as well as those in heterosexual relationships, and literature in this area is on the increase. However, there is still a scarcity of research exploring how the police respond to people who report same-sex partner abuse. Using a mixed-method feminist approach, the aim of this thesis was therefore to explore the police responses to same-sex partner abuse in England and Wales. The nature and extent of reported same-sex partner abuse crimes in England and Wales was explored via data gathered from Freedom of Information requests sent to police forces. Alongside these, one-to-one interviews were carried out with victims who had experienced police response (n=4), police officers and staff (n=19), and professionals from statutory and voluntary organisations who support victims (n=12). Findings suggested that a ‘process-driven’ approach was adopted by police; police generally stated that they respond in the same way to all partner abuse incidents. However, this meant that dynamics specific to same-sex relationships were sometimes overlooked. Perpetrators were also found to enact ‘pre-emptive coercive tactics’ to discourage victim help seeking, and cause them to fear a ‘coerced response’ from help-providers. Additionally, gender stereotypes were found to influence police decision making around attribution of blame and risk, with physical injury being the key indicator used to determine risk. Freedom of Information requests also indicated that roughly half of police forces in England and Wales provide little or no specialist support for same-sex partner abuse victims. Implications for policy and practice include a rethink of the process-driven way of working, and ensuring police possess a thorough understanding of coercive control (including risks unique to same-sex relationships). Combining innovative methodology and a variety of participant voices to examine an under-explored area, this thesis offers a unique contribution to a small body of research within the UK exploring police responses to same-sex partner abuse